Occasional Subject-nominations in the Artistic Discourse of Vasyl Barka (Linguostylistic Studies, 2017)
The article highlights the issues of the individual author's nominations in the novel «Rai» («Paradise») by Vasil Barka. The author analyzes the semantics, derivational structure and peculiar functioning features of authors’ noun-neologisms. The identified author’s neologisms are classified into three main lexico-semantic groups of neolexemes: the names of persons, nouns with abstract meaning, nouns denoting names of concrete subjects. The largest group of lexical innovations is represented by nouns with an abstract meaning. All the revealed noun neolexemes are created in accordance with the traditional word building patterns. The most productive ways of creating neolexemes in the novel are suffixation and composition. The key findings of the research prove that individual author’s noun-neologisms mainly perform the evaluative and expressive role in the novel «Paradise».
Keywords: neologism; author’s neologism; lexical innovation; individual author's nomination; neolexeme; compound word